Jacques Derrida e l’a-venire della psicoanalisi - Resta, Caterina (Bollettino Filosofico, 2021)
Derrida’s relationship with psychoanalysis is very complex. On the one hand, the deconstruction intends to unmask the metaphysical character of the Freudian conceptual apparatus, on the other, Derrida does not renounce to recognize the revolutionary character of psychoanalysis, that is, its vocation to be “knowledge without alibi”. Psychoanalysis today seems to be affected by a double resistance, external as well as internal, which prevents it from expressing its critical and subversive spirit. However, Derrida trusts in the to-come of psychoanalysis, provided that it deals with the great ethical, political and juridical transformations underway, starting from the crucial questions of cruelty and the instinct to master [Bemächtigungstrieb], which are at the origin of ipseity and the ghost of sovereignty. Keywords: Cruelty, Derrida, Instinct to Master [Bemächtigungstrieb], Psychoanalysis, Sovereignty